The Novel Actions of the Metabolite GnRH-(1-5) are Mediated by a G Protein-Coupled Receptor - Larco, Darwin O.; Semsarzadeh, Nina N.; Cho-Clark, Madelaine; Mani, Shaila; Wu, T John (Frontiers in Endocrinology, 2013)
The gonadotropin-releasing hormone (GnRH) was originally isolated from the mammalian hypothalamus for its role as the primary regulator of reproductive function. Since its discovery, GnRH has also been shown to be located in non-hypothalamic tissues and is known to have diverse functions. Although the regulation of GnRH synthesis and release has been extensively studied, there is additional evidence to suggest that the processing of GnRH to the metabolite GnRH-(1-5) represents another layer of regulation. The focus of this review will be on the current evidence for the action of the pentapeptide metabolite GnRH-(1-5) in regulating cellular migration. We discuss the potential role of GnRH-(1-5) in regulating GnRH neuronal migration during development. Furthermore, we demonstrate these actions are mediated by the activation of a G protein-coupled receptor (GPCR). Our findings suggest that GnRH-(1-5) may play a developmental function in addition to regulating developing cells.